The Comparison Effects of NaOH and KOH as Solvents for Silica Extraction from Two Different Coal Fly Ashes - Hanum, Farrah Fadhillah; Rahayu, Aster; Hapsauqi, Iqbal (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
One of the environmental problems is the waste from the coal combustion process from coal power plants or other industries that use coal as an energy source. The combustion process produces coal fly ash, which will accumulate in the environment. Subsequently, much research about the utilization of coal fly ash has been developed. Silica extraction from coal fly ash is one of the methods that can be used to utilize coal fly ash. This study carried out silica extraction using the Direct Alkaline Leaching (DAL) method. The coal ash was contacted with alkaline solvents (KOH and NaOH) with the variations of concentrations and the leaching time. The leaching solution filtrate will be precipitated with the addition of HCl. The characteristics of this silica from CFA and CFA B were analyzed by using Scanning Electron Microscopy (SEM). Based on the results, it could be known that each of the coal fly ashes has different results for both alkaline solvents. CFA A has relatively less silica extraction results in both types of solvents. Meanwhile, CFA B gave higher silica extraction results with coal fly ash and solvent contact time for one hour.